Company secretary characteristics and financial reporting timeliness: moderating role of the audit committee chairperson's accounting and industry expertise - Anwary Syuhaily, Rosly (2025)
Most studies in financial reporting timeliness have focused on the mechanisms of corporate governance and top management. However, studies on the role of the company secretary in financial reporting timeliness are limited, even though the role of the company secretary in the area is very critical. Consequently, this study examines the relationship between the characteristics of a company secretary, namely the role of duality, gender, ethnicity, age, tenure and financial expertise on financial reporting timeliness. Additionally, this study examines the audit committee chairperson's accounting and industry expertise as a moderator in the relationship between the characteristics of the company secretary and financial reporting timeliness. The sample for this study consisted of 594 observations of non-financial companies listed on the primary market of Bursa Malaysia from 2017 to 2022. This study employed Feasible Generalised Least Squares panel regression to analyse the data. The findings show that an older company secretary may increase the financial reporting timeliness. However, a dual role as a chief financial officer, a female company secretary and a long-tenured company secretary may reduce the financial reporting timeliness. Meanwhile, the ethnicity and financial expertise of the company secretary have no relationship with financial reporting timelines. In addition, audit committee chairs with accounting and industry expertise also moderate the relationship between gender and tenure of company secretary with financial reporting timeliness. The findings of this study provide insights to the government, regulators, legislators, professional bodies, investors, academicians and other users of financial reporting regarding the influence of the company secretary and the role of the audit committee chairperson on financial reporting timeliness. These could affect relevant laws, policies, and standards that seek to improve corporate governance.